Reality Counseling Technique To Improve Self-Happiness In Emerging Adulthood - Wahyuningtyas, Titik Angereni (EDUCOUNS GUIDANCE: Journal of Educational and Counseling Guidance, 2024)
The feelings, emotions, and pleasant energies that a person often experiences are the feelings that result from a happy mood, which is also associated with an increase in the joy of life for each individual. Few people can use their circumstances to generate good energy and work towards happiness, on the contrary, they prefer to be passive in an effort to improve the quality of their happiness. People feel that happiness is real and needs to be embodied as a source of inner strength when they see it as the primary means of navigating life. In essence, humans are creatures with basic needs in life that they want to meet, one of which is the need for pleasure. The background of the problem here is that some people are unable to meet their need for happiness. This reality-based approach is an intervention that helps people achieve their happiness goals. The goal of reality therapy is to enable people in the early stages of adulthood to meet their basic needs and live a happy life.